Algae utilization and its role in the development of green cities. (April 2021) - Chew, Kit Wayne; Khoo, Kuan Shiong; Foo, Hui Thung; Chia, Shir Reen; Walvekar, Rashmi; Lim, Siew Shee
Abstract: With the rapid urbanisation happening around the world followed by the massive demand for clean energy resources, green cities play a pivotal role in building a sustainable future for the people. The continuing depletion of natural resources has led to the development of renewable energy with algae as the promising source. The high growth rate of microalgae and their strong bio-fixation ability to convert CO2 into O2 have been gaining attention globally and intensive research has been conducted regarding the microalgae benefits. The focus on potential of microalgae in contributing to the development of green cities is rising. The advantage of microalgae is their ability to gather energy from sunlight and carbon dioxide, followed by transforming the nutrients into biomass and oxygen. This leads to the creation of green cities through algae cultivation as waste and renewable materials can be put to good use. The challenges that arise when using algae and the future prospect in terms of SDGs and economy will also be covered in this review. The future of green cities can be enhanced with the adaptation of algae as the source of renewable plants to create a better outlook of an algae green city. Graphical abstract: Image 1 Highlights: Developments of green cities with rich biodiversity and sustainable environment. Microalgae as a potential feedstock to achieving sustainable development goals. Algae can produce bioenergy and biofuel, while contributing to carbon sequestration. Creation of algae-powered buildings and cities for a greener future. Algae as a promising source for of carbon sink to reduce global warming.